Exercise Training Effects on Inflammatory Gene Expression in White Adipose Tissue of Young Mice - Tracy Baynard; Victoria J. Vieira-Potter; Rudy J. Valentine; Jeffrey A. Woods (Mediators of Inflammation)
We aimed to determine the effects of 6 wks of exercise on inflammatory markers in mice concomitantly fed either high-fat (HF) or normal chow (NC) diets in young mice. C57BL/6 mice were randomized into (/group) an NC/sedentary (NC/SED), NC/exercise (NC/EX), HF/SED, and HF/EX groups. Treadmill exercise was performed 5 d/wk at 12 m/min, with 12% grade for 40 min/d. Liver triglycerides and gene expression of F4/80, MCP-1, TNF-α, leptin, and VEGF in visceral white adipose were determined. NC groups had lower body weights after 6 wks versus the HF groups ( versus  g) (). F4/80 gene expression (indicator of macrophage infiltration) and liver triglycerides were greatest amongst the HF/SED group, with no differences between the remaining groups. VEGF (indicator of angiogenesis) was greatest in the HF/EX versus the other 3 groups (). Exposure of an HF diet in sedentary young mice increased visceral adipose depots and liver triglycerides versus an NC diet. Exercise training while on the HF diet protected against hepatic steatosis and possibly macrophage infiltration within white adipose tissue. This suggests that moderate exercise while on an HF diet can offer some level of protection early on in the development of obesity.